Співвідношення приватного та публічного інтересів у процесі реалізації митних режимів в Україні - Лемеха, Ростислав Ігорович; Лемеха, Р. І.; Lemekha, Rostyslav I.; Lemekha, R. I. (Одеса : Гельветика, 2020)
У науковій публікації досліджуються актуальні питання співвідношення приватного та публічного інтересів у процесі реалізації митних режимів в Україні. Зазначається, що у процесі реалізації митних режимів публічний інтерес органів публічної адміністрації в особі Державної митної служби України полягає в забезпеченні належного митного оформлення переміщення товарів та транспортних засобів через митний кордон України й ефективному здійсненні митного контролю дотримання норм Митного кодексу України й інших законодавчих актів суб’єктами зовнішньоекономічної діяльності. Водночас зазначеним публічним інтересам часто протистоїть приватний інтерес підприємців – суб’єктів зовнішньоекономічної діяльності мінімізувати розмір митних платежів або ухилитися від належного митного оформлення та контролю переміщення товарів і транспортних засобів через митний кордон України. Формулюється висновок про те, що чинне національне законодавство у сфері правового регулювання митних відносин потребує вдосконалення в напрямі забезпечення оптимального балансу між публічними та приватними інтересами. З огляду на нові виклики глобалізації та необхідність захисту національної економіки, створення нових робочих місць та підтримки національного виробника існує необхідність створення додаткових правових стимулів щодо розвитку митних режимів експорту, реекспорту та транзиту, а також переробки на митній території України. Особливу увагу органи публічної адміністрації повинні приділяти правовим засобам обмеження небажаного для національної економіки імпорту, застосовувати в необхідних випадках заходи нетарифного регулювання зовнішньоекономічної діяльності. Відзначається, що ефективний захист публічних інтересів у процесі реалізації митних режимів в Україні є гарантією реалізації приватних інтересів громадян України як кінцевих споживачів товарів, які імпортуються в Україну, щодо безпечного та якісного рівня життя.

The scientific publication is devoted to the topical issues of the ratio of private and public interests in the implementation of customs regimes in Ukraine. It is noted that in the process of implementation of customs regimes the public interest of public administration bodies represented by the State Customs Service of Ukraine is to ensure proper customs clearance of goods and vehicles across the customs border of Ukraine, professional performance of all customs procedures, quality administration of payment of all customs duties, in full and effective implementation of customs control of compliance with the Customs Code of Ukraine and other legislative acts by subjects of foreign economic activity. At the same time, these public interests are often opposed by the private interest of entrepreneurs to minimize the amount of customs duties or to evade proper customs clearance and control of movement of goods and vehicles across the customs border of Ukraine. Emphasis is placed on the fact that the legal regulation of customs regimes in Ukraine should be aimed at achieving an optimal balance between the public interests of Ukrainian society and the state and private interests of foreign economic activity, which provides favorable conditions for export and import of goods, transit and also the implementation of other customs regimes, taking into account the need to protect the interests of domestic producers, the rights of Ukrainian consumers to safe and quality products. The conclusion is formulated that the current national legislation in the field of legal regulation of customs relations needs to be improved in the direction of ensuring the optimal balance between public and private interests. Given the new challenges of globalization and the need to protect the national economy, create new jobs and support the national producer, there is a need to create additional legal incentives for the development of customs export, re-export and transit, as well as processing in the customs territory of Ukraine. Public administration bodies should pay special attention to legal means of restricting imports undesirable for the national economy, applying, where necessary, measures of non-tariff regulation of foreign economic activity. It is noted that the effective protection of public interests in the implementation of customs regimes in Ukraine is a guarantee of the private interests of Ukrainian citizens as final consumers of goods imported into Ukraine, for a safe and quality standard of living.
Лемеха Р. І. Співвідношення приватного та публічного інтересів у процесі реалізації митних режимів в Україні / Р. І. Лемеха // Юридичний вісник. - Одеса : Гельветика - 2020. - № 5. - С. 39-47.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; public interest; private interest; customs clearance; customs control; customs regimes; export; import; transit; legal incentives; protection of interests; non-tariff regulation; foreign economic activity; публічний інтерес; приватний інтерес; митне оформлення; митний контроль; митні режими; експорт; імпорт; транзит; правові стимули; захист інтересів; нетарифне регулювання; зовнішньоекономічна діяльність